en - Arini Hidayah; Asfi Aniuranti (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2022)
There are many kinds of entertainment that are popular among the people, one of which is music. Songs use language as a medium to convey ideas or meanings to people who listen to them. Many singers in Indonesia are born and famous. One of them is Ussy Sulistiawaty. Ussy Sulistiawaty is a singer who often mixes English into the lyrics of some of her songs. A linguistic practice that mixes two or more languages and includes each other's terms of language elements, such as words, in other languages consistently is called code-mixing. Sulistiawaty. The object of this research is the lyrics of the song Ussy Sulistiawaty. Data and data sources in the form of written data are contained in a collection of song lyrics by Ussy Sulistyawaty. The data collection technique is the note-taking method. These results are the most common code mixing found in Ussy Sulistiawaty's song lyrics, namely (1) English clause code mixing and (2) the background of the emergence of English code mixing in Ussy Sulistiawaty's song lyrics because it is to attract attention, entertain listeners, and research on language that is often used by teenagers today.